JEJAK – JEJAK RUMAH JAWA DALAM TRADISI INDONESIA LAMA - Martino Dwi Nugroho (Ars: Jurnal Seni Rupa dan Desain, 2009)
One of the result of culture which representing Indonesian resident creativity is architecture, in this case is Javanese house. [The] mentioned proved with many archaeological fact. Division of time dimension based to the Hindu Budha period and Islamic period. The data got from pictorial data, verbal data, and architectural data. Classic Javanese house, having marking: Building construction from wood representing pillar stand up above of land, having gallery of mine and without space winnow. Old Majapahit house, having marking : building construction from wood standing above batur and still there is no permanent constrictor. its Roof covered by tiles. Final Majapahit house, having characteristic : it is equal to Old Majapahit house but have had permanent constrictor. The Javanese house have building system called rumah kolong or rumah panggung. The Javanese house at Islamic period that is Yogyakarta Kingdom have started to recognize west technology that is with use of its material even conception Hindu still very obvious. Besides esthetics element start to be applied that is with use of the ornament. Besides knowledge about developing house start to be booked written of manuscript about technique making of Javanese house called kawruh kalang.Keywords: Javanese house, history, Javanese temples, pictorial data, verbal data, architectural data